FOXP3 as a prognostic marker and therapeutic target in immunogenic cell death modulation for clear cell renal cell carcinoma - Jian Chen; Cheng Zhu; Yan He; Liping Huang; Weizhuo Wang; Shuaishuai Huang (Discover Oncology)
Abstract Background Clear cell renal cell carcinoma (ccRCC) remains a challenging cancer type due to its resistance to standard treatments. Immunogenic cell death (ICD) has the potential to activate anti-tumor immunity, presenting a promising avenue for ccRCC therapies. Methods We analyzed data from GSE29609, TCGA-KIRC, and GSE159115 to identify ICD-related prognostic genes in ccRCC. By applying consensus clustering, patients were categorized based on ICD modification patterns, and an ICD signature (ICDS) model was developed using a PCA approach. Functional studies were conducted with FOXP3 knockdown in ccRCC cell lines to explore its impact on cell behavior. Results Eleven ICD-related genes were identified as key prognostic indicators in ccRCC, with high ICDS linked to worse survival outcomes. High ICDS also correlated with increased levels of immune-suppressive cells within the tumor microenvironment. FOXP3 was highlighted as a critical gene influencing ICD, where its knockdown significantly reduced ccRCC cell proliferation and migration, underscoring its role in tumor progression. Conclusions This study establishes FOXP3 as a pivotal factor in ICD regulation and ccRCC progression. Targeting FOXP3 and other ICD pathways could enhance treatment efficacy in ccRCC, providing a foundation for ICD-based therapeutic strategies. Evaluating ICD patterns in ccRCC may guide patient-specific interventions, paving the way for improved management of this aggressive cancer.